Development of professionally significant qualities of future economists by means of the hidden curriculum - SHCHERBATYKH, S.V.; MISHINA, S.V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The relevance of the research is determined by the necessity of the optimized training of future economists. The purpose of the research is to test experimentally a model for the formation of professionally significant qualities of future economists using the hidden curriculum technology. This article used the ascertaining experiment, formative experiment, questioning, testing, method of expert assessment, content analysis of the academic curriculum, and the mathematical statistics method. Results showed of the research identified the conditions for the development of the professionally significant qualities of future economists using the hidden curriculum technology. RESUMEN La relevancia de la investigación está determinada por la necesidad de la formación optimizada de los futuros economistas. El propósito de la investigación es probar experimentalmente un modelo para la formación de cualidades profesionalmente significativas de futuros economistas mediante la tecnología del currículum oculto. Este artículo utilizó el experimento de determinación, el experimento formativo, las preguntas, las pruebas, el método de evaluación experta y el método de estadística matemática. Los resultados mostrados de la investigación identificaron las condiciones para el desarrollo de las cualidades profesionalmente significativas de los futuros economistas a través de la tecnología del currículum oculto.